Development of Interactive Powerpoint Media to Stimulus the Ability to Recognize Flat Shape in Children Aged 5-6 Years - Della, Ellyta Iman; Ismail, Moh Hemli; Asriadi AM, Muh (Jurnal Smart Paud, 2024)
This research aims to develop a product to increase children's interest in learning and enrich the variety of learning media. The method used in this research is Design and Development (D&D) and in creating or developing products, researchers use the ADDIE model. The validation test results for interactive PowerPoint media from material experts showed a score of 3.6 in the "Very Feasible" category, while media experts gave a percentage of 3.9 in the "Very Feasible" category, and language experts gave a score of 3.3 in the "Decent" category. Therefore, interactive PowerPoint-based learning media is considered very feasible and meets the established standards. The results of the child's observations showed an N-Gain value of 0.8 in the "High" category with an N-Gain effectiveness interpretation of 84.6, including the "Effective" category. The results of the response test show that the average value of the recapitulation of responses from Teacher 1 and Teacher 2 shows a value of 3.8. It can be concluded that the media suitability assessment criteria developed are "Fully Implemented" which are effective for use in learning activities.